2020
DOI: 10.3758/s13423-020-01712-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency and accuracy of visual search develop at different rates from early childhood through early adulthood

Abstract: Most studies of visual search across the life span have focused on classic feature and conjunction searches in which observers search for a fixed, simple shape target among relatively homogeneous distractors over a block of multiple trials. In the present study, we examine a more realistic task in which participants (4 to 25 years-old) look for images of real objects, presented amongst a heterogeneous array of other objects. The target is unique on every trial, unlike in previous developmental studies of visua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 26 publications
4
19
0
Order By: Relevance
“…Again, as expected from previous studies, RTs were larger for set size 32 and target-absent conditions (refer to Table 4). The interaction was also significant: set size effects were larger under target-absent conditions, replicating previous results again (Gil-Gómez de Liaño et al, 2020).…”
Section: The E-operator Functioning: Reaction Times and Search Slopessupporting
confidence: 87%
See 3 more Smart Citations
“…Again, as expected from previous studies, RTs were larger for set size 32 and target-absent conditions (refer to Table 4). The interaction was also significant: set size effects were larger under target-absent conditions, replicating previous results again (Gil-Gómez de Liaño et al, 2020).…”
Section: The E-operator Functioning: Reaction Times and Search Slopessupporting
confidence: 87%
“…We recruited 191 participants from public and private elementary and middle schools in Madrid, Spain, and college students from Universidad Autónoma de Madrid. From previous studies on the lifespan in visual search (Gil-Gómez de Liaño et al, 2020), looking for age differences showed that with the alpha set to 0.05 and 1-beta (power) of over 0.9, we could detect significant effects (partial eta-square η 2 = 0.01) if we run between 21 and 33 participants per group of age. Thus, our sample size allowed for sizeable cohorts in each age, with a minimum of 21 for each age group (refer to Table 1).…”
Section: Participantsmentioning
confidence: 91%
See 2 more Smart Citations
“…Given that visual search performance changes with age, it is worth considering whether our findings are driven by these changes. The motor and executive functions required for efficient visual search improve rapidly in children around the ages tested in our study (Hommel et al, 2004; Gil-Gómez de Liaño et al, 2020). In particular, children are more susceptible to distractors compared to older adults despite having similar response times.…”
Section: Discussionmentioning
confidence: 73%